Electro-clinical features and management of the late stage of Lafora disease - d'Orsi, Giuseppe; Di Claudio, Maria Teresa; Palumbo, Orazio; Carella, Massimo (Frontiers in Neurology, 2022)
Purpose The aim of this study was to elucidate the electro-clinical features and management of the late stage of Lafora disease (LD). Methods We investigated the electro-clinical data and medical complications of three LD patients with mutations in EPM2A and two in NHLRC1 genes during the LD late stage. Results The late stage emerged after a mean period of 7 ± 1.41 years from the onset of the disease. All patients developed gait ataxia becoming bedbound with severe dementia. Pluri-monthly and drug-resistant myoclonic seizures, and myoclonic absence and tonic–clonic seizures were associated with daily/pluri-daily myoclonus, while the EEG/polygraphic findings showed diffusely slow activity with epileptiform abnormalities, often correlated with myoclonic jerks. Seizure emergencies with motor cluster/status epilepticus and medical complications dominated the clinical picture. In particular, video-EEG/polygraphic recordings disclosed status epilepticus with prominent motor symptoms of different subtypes refractory to IV new anti-seizure medications and responsive in 75% of cases to IV phenytoin. The main complications were dysphagia, aspiration pneumonia, acute respiratory failure, sepsis, immobility, and spasticity with bedsores. A coordinated and multidisciplinary management of the three patients with EPM2A mutations has demonstrated a reduction in seizure emergencies, medical complications and days of hospitalization, and a prolongation of the years of disease compared to the two patients with NHLRC1 mutations. Conclusion Status epilepticus with prominent motor symptoms of different subtypes, often responsive to IV phenytoin, and multiple medical complications characterize the LD late stage. An effective management requires a multidisciplinary medical and nursing team, coordinated by an epileptologist with the aim of reducing seizure emergencies and medical complications.